2023
DOI: 10.1002/smll.202302341
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oxygen‐Group‐Based Amorphous Nanomaterials in Electrocatalytic Water Splitting

Abstract: Environmentally friendly energy sources (e.g., hydrogen) require an urgent development targeting to address the problem of energy scarcity. Electrocatalytic water splitting is being explored as a convenient catalytic reaction in this context, and promising amorphous nanomaterials (ANMs) are receiving increasing attention due to their excellent catalytic properties.Oxygen group‐based amorphous nanomaterials (O‐ANMs) are an important component of the broad family of ANMs due to their unique amorphous structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…In comparison, it has been found that TMPi and TMPii show higher stabilities under electro-oxidation conditions. 27–30 Previous studies proposed that the flexible coordination of metaphosphate/phosphate ligands in TMPi/TMPii can stabilize the intermediate state of the transition metal by changing their local position with ease, hence facilitating water oxidation ( i.e. , OER).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, it has been found that TMPi and TMPii show higher stabilities under electro-oxidation conditions. 27–30 Previous studies proposed that the flexible coordination of metaphosphate/phosphate ligands in TMPi/TMPii can stabilize the intermediate state of the transition metal by changing their local position with ease, hence facilitating water oxidation ( i.e. , OER).…”
Section: Introductionmentioning
confidence: 99%